Cannabis use and myocarditis: a suspected association, emerging risk factor, and growing diagnostic challenge in young adults - Nakalamic, Natasa; Milicevic, Luka; Mihajlovic, Vladimir (Halo 194 Scientific Journal of Emergency Medicine, 2026)
Introduction: Acute myocarditis is a inflammatory injury of the myocardium, affecting 4–14 per 100,000 individuals. Several cases of marijuana-induced myocarditis have been reported. Cannabis contains THC, which exerts negative cardiotropic effects, including tachycardia, arrhythmias, blood pressure fluctuations, vasospasm, vasodilation, and increased risk of myocardial infarction.Case report: A 29-year-old male presented with palpitations and dyspnea and was admitted to the intensive care unit at the Cardiology Clinic, University Clinical Center Kragujevac. He had no history of acute infection or comorbidities but reported daily cannabinoid use for three months. Cardiac evaluation revealed multiple episodes of non-sustained ventricular tachycardia (nsVT). Cardiac magnetic resonance confirmed myocarditis. In the absence of other etiological factors, marijuana use was considered the most probable cause.Conclusion: Myocarditis of unknown origin in young patients requires a targeted diagnostic approach. Standard protocols should include screening for psychoactive substance use, given its prevalence and potential cardiovascular effects.
Keywords: myocarditis; cannabis; nsVT